Odyssey Self Reflection - Journey / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
The idea of bamboo weaving had inspired me to create artworks that consist of painting, printmaking, sculpture and drawing technique. The concept of my artworks is inspired by the technique of weaving bamboo and reflected my life’s journey. I work with the bamboo weaving technique into my sculpture. The intaglio technique was applied in my printmaking artwork.